Optimizing Tax and Production Efficiency: Strategic Cost Driver Analysis in Management Implementation Using Quantitative Assessment - Sahara, Khasanah; Putri, Trianita Kusuma (Universitas Islam Kadiri, 2025)
Introduction/Main Objectives: As a printing company in Kediri, CV. Surya Digital Printing needs to manage costs strategically to increase profitability and accurately meet tax obligations. This is very important for CV. Surya Digital Printing to increase profitability using the ABC system (Activity-Based Costing system). Background Problems: One of the main challenges is production cost efficiency and compliance with tax regulations. The company's profit is significant even though later with a large profit the tax payable is also significant the company is not harmed because with a cost driver the company's profit is indeed significant, the tax payable is also larger but the increase in profit is not as significant as the increase in tax payable. Novelty: This research offers a new approach by integrating cost driver analysis in the Activity-Based Costing (ABC) system to assess the efficiency of production costs and calculate their impact on the taxes owed by companies. Research Methods: The method used is descriptive, using data from 2022 and 2023. The analysis is carried out by identifying production activities, classifying costs based on activities, determining cost drivers, and calculating rates per unit cost driver to assess cost efficiency and calculate taxes payable. Finding/Results: The study results show that applying cost driver analysis resulted in production cost efficiency of IDR 3,292,313,428. This efficiency increased the company's net profit and increased the tax payable from IDR 235,634,151.50 to IDR 597,788,628.58. Although taxes increased, the profit increase was much more significant, so the company still made a larger net profit. Conclusion: Cost driver analysis has proven effective in reducing cost distortions and improving the accuracy of production cost allocation. Implementing this strategy improves operational efficiency and supports better tax compliance without incurring sanctions or fines. Research limitations/implications: This study is limited to analyzing cost drivers in production costs without further exploring labor costs and overhead.